2005
DOI: 10.1038/sj.ijo.0802928
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic drug-induced weight gain: development of an animal model

Abstract: OBJECTIVE: Weight gain is a prominent effect of most atypical antipsychotic drugs (AAPDs); yet, the mechanisms are not fully understood and no well-established mouse models exist for investigating the mechanisms. Thus, we developed a mouse model to evaluate the effects of AAPDs on eating, body weight (BW), and body composition. METHODS: Female C57BL/6J mice were used to test olanzapine, quetiapine, ziprasidone, and risperidone. Mice were acclimated to individual housing, given ad libitum access to chow and wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 32 publications
9
80
0
Order By: Relevance
“…Chronic risperidone treatment lead to increases in both body weight gain and food intake in female rats (Baptista et al, 2002b andPouzet et al, 2003). A similar effect on body weight gain was observed in risperidone-treated female mice but without any accompanying increase in food intake (Cope et al, 2005). In contrast to the commonly observed body weight gain in female rodents, haloperidol or risperidone did not induce body weight gain in male rats (Baptista et al, 2002b andPouzet et al, 2003).…”
Section: Introductionmentioning
confidence: 84%
“…Chronic risperidone treatment lead to increases in both body weight gain and food intake in female rats (Baptista et al, 2002b andPouzet et al, 2003). A similar effect on body weight gain was observed in risperidone-treated female mice but without any accompanying increase in food intake (Cope et al, 2005). In contrast to the commonly observed body weight gain in female rodents, haloperidol or risperidone did not induce body weight gain in male rats (Baptista et al, 2002b andPouzet et al, 2003).…”
Section: Introductionmentioning
confidence: 84%
“…Antipsychotic drugassociated weight gain in a male rodent model has been shown by Minet-Ringuet et al (2006); however, clozapine has not been found to induce weight gain or metabolic abnormalities in female rats, but was found to increase adiposity (Cooper et al, 2007). Although antipsychotic drugassociated weight gain in rodent models is in dispute in regard to sex, drug administration, diet, dose, and antipsychotic agents used, the use of OLZ in female rats has consistently been demonstrated to reproduce the weight gain, increased adiposity, and metabolic disturbances seen in patients (Albaugh et al, 2006;Arjona et al, 2004;Coccurello et al, 2006;Cooper et al, 2005;Cope et al, 2005;Goudie et al, 2002;Raskind et al, 2007). With a similar rodent model, we have shown that ZNS both inhibits and reverses SGA-associated hyperphagia, weight gain, and increased feed efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…SGAs such as olanzapine (OLZ) have been found to cause rapid and pronounced hyperphagia in both rodents Cope et al, 2005) and humans (Brixner et al, 2006;Goudie et al, 2005). One hypothetical pathway for this dramatic increase in food consumption may be the activation of orexin neurons in the lateral hypothalamus (LH), and in turn, the release of neuropeptides known to be critical in body weight regulation (Fadel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Observational preclinical (Thornton-Jones et al, 2002;Ota et al, 2002;Hartfield et al, 2003a;Arjona et al, 2004;Cope et al, 2005) and clinical data suggest that one of the ways SGAs can lead to changes in the patterns of food intake is by increasing appetite (Figure 5b; Bromel et al, 1998;Briffa and Meehan, 1998;Eder et al, 2001;Basson et al, 2001;Kinon et al, 2005) and subsequent consumption of the previously preferred diet (Gothelf et al, 2002;Kane et al, 2004).…”
Section: Effects Of Sgas On Food Intakementioning
confidence: 99%